Bringing early colonial astronomy to life. Issue 2 (1st April 2021) - Ridley, Anna
Abstract : Anna Ridley describes a new exhibition at Old Government House, Sydney, that uses documents from the Royal Astronomical Society library and archive – and technology – to help tell the story of scientific endeavour in colonial New South Wales Abstract: Anna Ridley describes a new exhibition at Old Government House, Sydney, that uses documents from the Royal Astronomical Society library and archive – and technology – to help tell the story of scientific endeavour in colonial New South Wales